A novel multiparametric flow cytometry-based cytotoxicity assay simultaneously immunophenotypes effector cells: Comparisons to a 4 h 51Cr-release assay - Kim, G.G.; Donnenberg, V.S.; Donnenberg, A.D.; Gooding, W.; Whiteside, T.L. (Journal of immunological methods, 2007)
Natural killer (NK) cell-or T cell-mediated cytotoxicity traditionally is measured in 4–16 h 51Cr-release assays (CRA). A new four-color flow cytometry-based cytotoxicity assay (FCC) was developed to simultaneously measure NK cell cytotoxicity and NK cell phenotype (CD3 -CD16 +CD56 +). Target cells, K562 or Daudi, were labeled with Cell Tracker Orange (CTO) prior to the addition of effector cells. Following co-incubation, 7 amino-actinomycin D (7-AAD) was added to measure death of target cells. The phenotype of effectors, viability of targets, the formation of tumor-effector cell conjugates and absolute numbers of all cells were measured based on light scatter (FSC/SSC), double discrimination of the fluorescence peak integral and height, and fluorescence intensity. Kinetic studies (0.5 and 1 to 4 h) at different effector to target ( E: T) cell ratios (50, 25, 12, and 6) confirmed that the 3 h incubation was optimal. The FCC assay is more sensitive than the CRA, has a coefficient of variation (CV) 8-13% and reliably measures NK cell-or lymphokine-activated killer (LAK) cell-mediated killing of target cells in normal controls and subjects with cancer. The FCC assay can be used to study a range of phenotypic attributes, in addition to lytic activity of various subsets of effector cells, without radioactive tracers and thus, it is relatively inexpensive. The FCC assay has a potential for providing information about molecular interactions underlying target cell lysis and thus becoming a major tool for studies of disease pathogenesis as well as development of novel immune therapies.